Assessment of steel corrosion caused by pre-existing microorganism in produced water from an oil and gas facilities and its inhibition using glutaraldehyde / Mohamad Hikmal Azeem Shaharudin, Nor Roslina Rosli and Nik Raihan Nik Him - Shaharudin, Mohamad Hikmal Azeem; Rosli, Nor Roslina; Nik Him, Nik Raihan (Universiti Teknologi MARA, 2021)
Microbiologically induced corrosion (MIC) is defined as corrosion caused by the activity of microorganisms which contribute to the high annual cost in oil and gas industries. Abundant microbial flora can be found in oil field formation waters which makes MIC inevitable. This brief preliminary study involves the growth of the microbes obtained from produced water sample from an oil and gas facility. Their corrosion activities on AISI 1018 carbon steel were also studied, including the utilization of glutaraldehyde as a corrosion inhibitor. The microbial growth was conducted on solid agar and liquid nutrient medium. The bio screening procedures were done by measuring the optical density using spectrophotometer and measurement of microbe dry weight. Laboratory scale corrosion test was conducted using weight loss method in simulated field condition. Glutaraldehyde was added in varying concentrations from 50 to 200 ppm to determine its effective dosage. The growth of colorless bacteria was observed in the agar medium, validated by the increased optical density in the liquid broth. The colorless bacteria were suspected as Sulphur oxidizing bacteria (SOB) which is the main type of microbe that occurs in water. SOB induces corrosion in metal pipelines due to its oxidation reaction of Sulphur compounds. The corrosion rate measured was 0.59 mm/year. The addition of 200 ppm of glutaraldehyde recorded the lowest corrosion rate which was 0.24 mm/year. It can be concluded that water sample from oil and gas field contained bacteria that causes MIC and can be controlled using glutaraldehyde, which has strong antibacterial and antifungal properties.